Analysis of the Establishment of the Regional Technical Implementation Unit for the Animal Health Center (UPTD Puskeswan) for the Food Crops, Horticulture and Livestock Service Office in Mamuju Regency - Ma'ruf, Muchammad Achsinul Fikri; Al-Arif, Mohammad Anam; Lokapirnasari, Widya Paramita; Hidanah, Sri (Universitas Airlangga, 2023)
The purpose of this study was a strategy in designing the establishment of the Regional Technical Implementation Unit for Animal Health Centers (UPTD Puskeswan) in order to optimize animal health services in Mamuju Regency. This study used an exploratory method using a survey. The sampling technique in this study used questionnaires, documentation and interviews. There were 10 samples of respondents from animal health workers and 100 samples of service users. Data analysis in this study used SWOT analysis. The appropriate strategy to support animal health services is a rapid growth strategy with alternative strategies: (1) strength-opportunity (SO) to improve service quality, service quantity and support the operational needs of officers in carrying out activities; (2) strength-threat (ST) implementing service SOP for animal health officers so that services are more efficient and systematic; (3) weakness-opportunity (WO) socialization of services to facilitate information to the public; and (4) weakness-threat (WT) making long-term planning to improve work ethic and understanding of drug use by veterinary officers.